Resilience of Islamic Religious Education (PAI) Teachers in the Hyperconnected Era in Addressing Students’ Low Learning Interest - M. All Mujakir; Ruslan Ruslan; Ihlas Ihlas (Journal of Islamic Education Students (JIES), 2026)
This study aims to analyze the resilience of Islamic Religious Education (PAI) teachers in the era of hyperconnected society in overcoming the problem of low student interest in learning. The rapid development of digital technology, intensive use of social media, and constant online connectivity have affected students' learning patterns and often reduced their focus and involvement in the classroom learning process. This condition requires teachers to have adaptability, innovative pedagogical strategies, and professional and emotional resilience so that learning continues to take place effectively and meaningfully. This research uses a qualitative approach with a descriptive-analytical design. Data was collected through learning observations, in-depth interviews, and documentation involving PAI teachers as the main participants. Data analysis is carried out through the process of coding, categorization, and theme discovery using the help of NVivo software to systematically identify patterns and relationships between data. The results of the study show that the resilience of PAI teachers is reflected in the ability to adapt to technological developments, the effective use of digital learning media, the implementation of interactive and reflective learning strategies, and professional commitment in facing learning challenges in an increasingly digitally connected environment. These findings confirm that teacher resilience has a strategic role in increasing student engagement and interest in learning and supporting a more adaptive PAI learning quality in the digital era.